COMMUNITY PARTICIPATION AND THE DEVELOPMENT PROCESS IN REGIONS IN STATE ADMINISTRATIVE LEGAL PERSPECTIVE - Syuhada, Otong (Fakultas Hukum Universitas Djuanda, 2024)
Improvement of an area can be the main effort to improve people's welfare. In practice, community inclusion is one of the most important factors, and the main thing is arrangements with improvements based on the scale of needs. In Law Number 25 of 2000 concerning the National Development Program (Propenas) it is stated that the regional promotion approach is coordinated to realize broad, genuine and reliable regional independence in the system of community strengthening, self-directed education, political education, legal education, religious education, conventional education, and non-governmental organizations within the Unitary State of the Republic of Indonesia. The concept of a welfare state is briefly characterized as a country whose government is considered to have the vision to guarantee the lowest level of welfare for every citizen. It considers the points for viewing and analyzing the degree of open inclusion in preparation for progress in the regions from the point of view of the State Authority Act. The strategy used in this thinking is sociological juridical with a statutory and contextual approach, while the information used is additional information. From the results of the consideration, several forms of open association were found in handling regional progress, such as through the Recess Program carried out by each part of the DPRD in the form of training in the form of open meetings with the community (constituents) and the Development Planning Deliberation program carried out by the government by involving all components of society from each level and profession.